Milk and Dairy Foods Improve Nutrient Intakes Among Children in Australia, Russia and the US (P18-097-19). (13th June 2019) - Eldridge, Alison; Semenova, Iaroslava; Bryantseva, Sofia; Martinchik, Arseniy; Keshabyants, Evelina; Fayet-Moore, Flavia; McConnell, Andrew; Fulgoni, Victor
Abstract: Objectives: Milk and dairy foods are typically the biggest contributors to calcium in the diets of children who consume them. Our objective was to explore consumption patterns of milk and dairy foods from children in three countries (Australia, Russia and the US) and to evaluate the nutritional impact of milk and dairy foods in these diverse geographies. Methods: National survey data were used to evaluate milk and dairy consumption among 4–12 y old children. Data sources included the 2011–12 Australian National Nutrition and Physical Activity Survey (NNPAS) ( n = 1576), the 2013 Russian National Nutrition Survey ( n = 22, 410), and the 2013–2016 US National Health and Nutrition Examination Survey (NHANES) ( n = 3343). Food groups were created for Milk, Fermented Dairy (including yogurt and kefir), Cheese and Total Dairy. Serving sizes were standardized so comparisons could be made. Percent consuming and amounts per capita and per consumer were calculated. Usual nutrient intakes were estimated for children receiving ≥ 2 servings/d, compared to 1 to <2 servings, 0 to <1 serving and none for each of the dairy groups. Results: Dairy consumption was high in Australia (83.2%), Russia (91.5%) and the US (81.6%). Milk consumption ranged from 69.5% (US) to 70.7% (Australia) and 82.5% (Russia). Fermented dairy was consumed by 10.1%, 17.7% and 29.6%, and cheese by 35.8%, 36.5% and 40.0% of children in US, Australia and Russia, respectively. While Russia reported the highest prevalence, per capita consumption (g) was highest and energy intake (kcal) was lowest in the US. Local recommendations differ, but only about 24% of children consumed ≥2 servings of dairy/d, with 14% (Australia), 6% (Russia) and 15% (US) reaching 2 servings/d from milk alone. Dairy foods provided approximately 11% of total daily energy (milk alone, 8%), but among those consuming ≥2 servings/d, dairy foods contributed 23% of total daily energy (milk alone, 20%). Nutrient intakes were consistently higher for children in the higher dairy consumption categories, especially for calcium, phosphorus, and vitamins A and D where milk is fortified. Conclusions: Milk and dairy foods make important contributions to daily nutrient intakes in 4–12 y old children. Dairy consumption should be encouraged, as few children actually consume dairy foods according to local recommendations. Funding Sources: Analysis of the national survey data used in this abstract was sponsored by Nestlé Research, Vers-chez-les-Blanc, Lausanne, Switzerland.